Contribution of islamic education learning to improving the quality of student character - Anaas Tri Ridlo Dina Yuliana; Tri Yaumil Falikah; Zalik Nuryana; Fitria Sari Yunianti (At Turots: Jurnal Pendidikan Islam, 2024)
The process of learning activities is now increasingly varied and developing following advances in various fields of science, but not all teachers are willing or able to utilize these various learning methods. This problem occurs especially in the fields of social and religious sciences which are mostly guided by textbook texts without any initiative by teachers to develop contextually during the learning process, so that the essence of the learning material cannot be understood by students. Apart from that, technological advances have given rise to moral problems that are at an alarming level. This issue is related to Islamic religious education learning activities and their implications for the quality of student character, so evaluation is needed in the form of research and assessment as material for reflection on the results of implementing the PAI learning process on the quality of student character. This research aims to analyze the relationship and influence of PAI learning with improving the quality of student character. The research approach uses correlational quantitative methods. The population is 99 students in class XI at SMK Muhammadiyah 1 Wates. Sampling used saturated sampling, and questionnaires as data collection techniques. The data analysis techniques use descriptive and inferential. Descriptive analysis techniques include frequency analysis and cross tables, while inferential analysis techniques include correlation analysis and simple linear regression. The research results show that the contribution of PAI learning to improving the quality of students' character is positive and significant, and the correlation coefficient value is 0.542 in the medium category. The influence of PAI learning on the quality of students' character is 29.4%